Gestão e execução do Programa Nacional de Alimentação Escolar nos Institutos Federais de Educação, Ciência e Tecnologia - Costa, Paula Medeiros (2015)
The Nacional School Feeding Programme (NSFP), one of the most important public politics of feeding and nutrition in Brazil, aim to promote Food and Nutritional Security and ensure to the basic education students the right of having free, nutritive, healthy and higienic food during the whole school year. Considering the importance of school feeding for students, this project aim to analyze the management and enforcement of The Nacional School Feeding Programme in the Federal Institutes of Education, Cience and Tecnology. This Project is a transversal study, the data collection happened in the second semestre of 2014 by phone call interviews in 203 Campi of the Institutes, distributed proportionaly in brasilian macro-regions.The descriptive variables were expressed in relative and absolute frequency. For variables comparision (Campi with and without nutritionist) Pearson x2 tests were held with Yates correction or Fisher Exato. In order to measure the variables association magnitude with p<0,05, the prevalence reason were calculated. In order to investigate the numeric variable simetry the Shapiro – Wilk normality test was used and then the median was calculated. The statistic significance level of 5% was considered. The results indicated that 22,16% of the Campi received the NSFP resources and among these 27 had nutritionist. Among the Campi that received the resources 46,7% bought familiar agriculture supriment , 60% had food and nutritional education activities, 40% have an especific menu for the programme, 71,1% show the menu to the students, 46,7% offer diferente food for students with special nutritional needs and 51,1% make acceptability tests. It was concluded that few Campi received financial resources of the Scholar Food Nacional Program and that the presence of the nutricionist, even without contributing efectivelly in the resource reception, favored to make the food and nutrition educational activities, one of the main axis of the program.